2021
DOI: 10.3390/genes12040485
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite DNA Analysis of Genetic Diversity and Parentage Testing in the Popular Dog Breeds in Poland

Abstract: There is growing concern that extreme breed standardization contributes to a reduction of the effective population size and high levels of inbreeding, resulting in the loss of genetic diversity in many breeds. This study examined genetic diversity among eight popular dog breeds in Poland and evaluated the effectiveness of a 21-microsatellite (STR) panel recommended by the International Society for Animal Genetics (ISAG) for parent verification. The following breeds were characterized: German Shepherd, Maltese,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The results show that the breed has a high level of genetic diversity. The number of alleles that have the greatest genetic influence on heterozygosity, known as Ne, averaged 4.869 in the general population, which is higher than the Ne reported for other native dog breeds: 3.0-3.5 for the Italian Greyhound [28], 3.3 for the German Shepherd, 3.5 for the Maltese, 3.2 for the Biewer Yorkshire Terrier, 3.5 for the Yorkshire Terrier [29]. All markers were highly informative (PIC values greater than 0.5) [30], suggesting the efficacy of these markers for the assessment of genetic variation among the Tazy dogs.…”
Section: Discussionmentioning
confidence: 72%
“…The results show that the breed has a high level of genetic diversity. The number of alleles that have the greatest genetic influence on heterozygosity, known as Ne, averaged 4.869 in the general population, which is higher than the Ne reported for other native dog breeds: 3.0-3.5 for the Italian Greyhound [28], 3.3 for the German Shepherd, 3.5 for the Maltese, 3.2 for the Biewer Yorkshire Terrier, 3.5 for the Yorkshire Terrier [29]. All markers were highly informative (PIC values greater than 0.5) [30], suggesting the efficacy of these markers for the assessment of genetic variation among the Tazy dogs.…”
Section: Discussionmentioning
confidence: 72%
“…Although pedigree data are important for determining genetic diversity, they are limited by the start of recording and missing or incorrect recordings [ 20 ]. The availability of genomic data has facilitated landscape genomics and conservation studies to accurately estimate genetic diversity and inbreeding [ 8 , 21 , 22 ]. Genomic data enable the accurate assessment of a population structure based on the actual versus expected genetic diversity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their study indicated that the tested Tatra shepherd dog population was highly polymorphic. In another study [ 29 ], eight breeds of dog were surveyed by 21 microsatellite markers. PIC values over 0.5 were measured for 15 markers.…”
Section: Discussionmentioning
confidence: 99%